DEBT TO EQUITY RATIO DAN CURRENT RATIO DALAM MENENTUKAN HARGA SAHAM MELALUI RETURN ON ASSET PADA PERUSAHAAN PERTAMBANGAN SUB SEKTOR BATU BARA TBK DI BEI TAHUN 2018-2021 - Syah, Aditiya Risqiyanto; Wahyuni, Ika; Subaida, Ida (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
Mining companies are companies that engage in various production activities such as general research, exploration, feasibility studies, construction, mining, management and refining, transportation and sales, as well as post-mining management. Mining companies are one of the main contributors to Indonesia's foreign exchange earnings. The purpose of this research is to analyze and determine the impact of Debt to Equity Ratio and Current Ratio on stock prices through Return on Assets in the coal mining sub-sector of the Indonesia Stock Exchange. The analysis and testing method used in this research is the Structural Equation Modeling - Partial Least Square (PLS-SEM). The hypothesis testing results using Smart PLS 3.0 application indicate that Debt to Equity Ratio has a postive but not significant effect on Return on Assets. Current Ratio has a negative and not significant effect on Return on Assets. Debt to Equity Ratio has a positive and significant effect on stock prices. Current Ratio has a negative and not significant effect on stock prices. Return On Assets has a positive but not significant effect on stock prices. The indirect hypothesis testing results show that Debt to Equity Ratio has a positive but not significant effect on stock prices through Return on Assets, and Current Ratio has a negative and not significant effect on stock prices through Return On Assets.